Analyzing Contextual Levels and Applications of Technological Pedagogical Content Knowledge (TPACK) in English as a Second Language Subject Area: A Systematic Literature Review - Greene, Moe D.; Jones, William M. (Educational Technology ＆ Society, 2020)
Technological pedagogical content knowledge (TPACK) defines the knowledge domains required for successful technology integration. Context is identified as an important component of TPACK. The aim of this systematic literature review was to examine context levels and the application of TPACK in the area of English language teaching and learning. The empirical studies reviewed were published between 2009 and 2019. Initial database searches yielded 365 results from which 24 articles were included in the final content analysis. Analysis of the included studies revealed that classroom factors at the micro contextual level were addressed more frequently than those at the meso and macro contextual levels, which were frequently not taken into consideration in the definition and explanation of TPACK. The majority of studies used qualitative methods for data collection which were also commonly determined through self-reporting. When self-reporting is used, TPACK is exclusively viewed as knowledge that teachers possess regardless of their context. The data indicate that teacher's contextual factors such as dispositions are not always included in the operationalization of TPACK. Teachers' contextual factors highlight their perspectives and belief systems. A critical perspective of teacher's TPACK knowledge development across contexts and the roles teachers are assigned in the classroom are vital to understanding the paradigm shifts that inform teachers' practices and training.